2019
DOI: 10.1002/2211-5463.12743
|View full text |Cite
|
Sign up to set email alerts
|

The iron–sulfur‐containing HypC‐HypD scaffold complex of the [NiFe]‐hydrogenase maturation machinery is an ATPase

Abstract: HypD and HypC, or its paralogue HybG in Escherichia coli, form the core of the scaffold complex that synthesizes the Fe(CN)2CO component of the bimetallic NiFe‐cofactor of [NiFe]‐hydrogenase. We show here that purified HypC‐HypD and HybG‐HypD complexes catalyse hydrolysis of ATP to ADP (kcat ≅ 0.85·s−1); the ATPase activity of the individual proteins was between 5‐ and 10‐fold lower than that of the complex. Pre‐incubation of HypD with ATP was necessary to restore full activity upon addition of HybG. The conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Protein film electrochemistry (PFE) has been shown to be a powerful technique to probe the redox biochemistry of such protoncoupled electron transfer reactions (Armstrong et al, 1997;Hirst, 2006;Fourmond and Léger, 2017). As we have demonstrated previously (Adamson et al, 2017b), Escherichia coli hydrogenase maturation factor HypD (elsewhere "H2ase-MFHypD"), an enzyme which is important in the biosynthesis of hydrogenases (Nutschan et al, 2019), acts as a relatively simple example of such biological proton-coupled electron transfer redox chemistry. When H2ase-MFHypD was immobilized on a graphite electrode we could use both classical direct current cyclic voltammetry (DCV, involving a linear potential-time ramp) as well as large amplitude Fourier transform alternating current voltammetry (FTACV, utilizing a sine-wave plus linearramp voltage-time oscillation) to observe reversible disulfide bond reductive cleavage and oxidative formation (Supplementary Figure S1), a reaction that is considered to be a net two-proton, two-electron reaction at near-neutral pH (Figure 1A) (Adamson et al, 2017b).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Protein film electrochemistry (PFE) has been shown to be a powerful technique to probe the redox biochemistry of such protoncoupled electron transfer reactions (Armstrong et al, 1997;Hirst, 2006;Fourmond and Léger, 2017). As we have demonstrated previously (Adamson et al, 2017b), Escherichia coli hydrogenase maturation factor HypD (elsewhere "H2ase-MFHypD"), an enzyme which is important in the biosynthesis of hydrogenases (Nutschan et al, 2019), acts as a relatively simple example of such biological proton-coupled electron transfer redox chemistry. When H2ase-MFHypD was immobilized on a graphite electrode we could use both classical direct current cyclic voltammetry (DCV, involving a linear potential-time ramp) as well as large amplitude Fourier transform alternating current voltammetry (FTACV, utilizing a sine-wave plus linearramp voltage-time oscillation) to observe reversible disulfide bond reductive cleavage and oxidative formation (Supplementary Figure S1), a reaction that is considered to be a net two-proton, two-electron reaction at near-neutral pH (Figure 1A) (Adamson et al, 2017b).…”
Section: Introductionmentioning
confidence: 91%
“…In this study, although H2ase-MFHypD serves as an extremely useful test system for developing our data analysis techniques for probing disulfide mechanisms, it is not possible to conclude if this redox-driven bond making/breaking is relevant to the physiological function of the enzyme ( Adamson et al, 2017b ; Nutschan et al, 2019 ). However, there are a multitude of proteins and enzymes where the disulfide chemistry is vitally important and in vitro electrochemical studies do provide a useful insight into the in vivo biological chemistry, as demonstrated by the comprehensive study by Bewley et al ( Bewley et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the Fe(CN) 2 (CO) moiety is assembled with the aid of the HypE and HypF proteins, which synthesize the cyanide ligands out of carbamoyl phosphate (Blokesch et al, 2004; Reissmann et al, 2003). The metabolic origin of CO under anaerobic conditions remains, however, unclear (Bürstel et al, 2011; Nutschan, Golbik, & Sawers, 2019), while under aerobic conditions, this diatomic ligand is derived from formyltetrahydrofolate (Bürstel et al, 2016; Schulz et al, 2020). Assembly takes place on a scaffold complex, consisting of the HypC and HypD proteins, from which the Fe(CN) 2 (CO) moiety is transferred to the apo‐large subunit (Bürstel et al, 2012; Stripp et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our working hypothesis comprises reduction in CO 2 with 2 e − and 2 H + to CO and H 2 O as catalyzed by the HypCD complex; however, the proposed reaction requires a low redox potential (E 0 ′ ≈ −530 mV). It has been demonstrated that the HypCD complex catalyzes the hydrolysis of ATP [ 21 ], which would help to overcome such thermodynamic barriers, not unlike CO dehydrogenase [ 59 ], the ‘iron protein’ of nitrogenase [ 60 ], or enoyl-CoA reductase [ 61 ]. Under aerobic conditions, the CO ligand is generated by decarbonylating formyltetrahydrofolate [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) The HypCD complex may catalyze an ATP-dependent reduction of CO 2 to CO at the expense of 1 eq. of H 2 O (21). The source of electrons required for the reduction of CO 2 to CO is unknown.…”
Section: Introductionmentioning
confidence: 99%